Ice recrystallization inhibition of commercial κ-, ι-, and λ-carrageenans. (February 2021) - Kiran-Yildirim, Bercem; Hale, Julia; Wefers, Daniel; Gaukel, Volker
Abstract: In this study, the structural composition of commercial kappa (κ)-, iota (ι)-, lambda (λ)-carrageenans was examined by using 1 H NMR spectroscopy, and the IRI activity of these different carrageenan samples was examined in sucrose solution. The 1 H NMR spectra showed that both λ-carrageenans consist of κ- and ι-units which are either present as a mixture of the two carrageenan types or as a κ/ι-copolymer. According to the IRI activity results, κ-carrageenan samples showed the highest IRI activity among the different carrageenans. In the presence of κ-carrageenan, the round ice crystals transformed into a more angular and elongated shape, while this effect was less visible in the presence of the ι- and λ-carrageenans. Viscosity measurements indicated that there is no correlation between the viscosity and the IRI activity of carrageenans. The IRI activities of the investigated carrageenans are different for the suppliers, and the results show that they are based on the structural differences and possibly also other compositional differences. Highlights: Investigation of the structural composition of different commercial carrageenans. Recrystallization inhibition activity depends on type of carrageenans and supplier. κ-carrageenan showed the highest IRI activity among the different carrageenans in sucrose solution. Recrystallization inhibition activities of structurally different carrageenans are not correlated with solution viscosity.